Otimização da pigmentação da gema do ovo: Lígia Mara Sandeski. - - Sandeski, Lígia Mara [UNESP] (2013)
The color of the egg yolk depends on the absorption and the deposition of carotenoids present in the hens´ diets and represents a sensory characteristic of great impact on the product acceptance. Corn is commonly used as energy value ingredient for hens´ diets formulations. Moreover, due to its additional pigmentation properties, it might be used to color egg yolk. The purpose of this research was to optimize the proportions between yellow and red pigments in hens´ corn based rations to provide color maximization for yolks. Sixty Dekalbe laying hens were separately distributed in cages inside a rearing barn to receive the experimental diets for 21 days at a daily feeding of 110 g and water ad libitum. Fifteen treatments were defined by means of a central composite rotatable design in which the variables were the yellow pigments from the diets (corn + gluten meal), the yellow supplementary pigments (lutein + zeaxanthin) and the red supplementary pigments (cantaxanthin), each of them at three different concentrations. Hens´ weights were recorded at the beginning and at the end of the experiment and the eggs weights were recorded daily. Yolks colors were determined by means of objective (L, a, b) and subjective (color fan) measurements. Global acceptance of yolks color was investigated with a five points hedonic scale. The results were analyzed by ANOVA, means comparison tests (t test and Dunn test) and regression analysis by Response Surface Methodology, at 5% significance level. Hens` final weights and eggs weights were not influenced by the treatments. Seven distinct colors for yolks were identified with the color fan. The most preferred yolks scored 9 and derived from the treatment which provided the highest yellow pigments concentrations (2.0 mg/hen/day) and no red pigments while the most rejected yolks scored 14 and derived from treatments which provided the highest concentration of red pigment (0.7 mg/hen/day), besides the yellow...